Polyphenols - Wong, Janica (IntechOpen, 2018)
Polyphenols, which mostly contain phenol structures, are phytochemicals found naturally in many types of food such as nuts, cocoa, berries, tea, and red wine. Emerging studies have shown that polyphenols can have multiple beneficial effects on the human body, such as antioxidative, anticancer, and antidiabetic effects. The present book encompasses many key aspects of polyphenolsfrom classification, dietary sources, health benefits, to possible mechanisms of action. "Polyphenols" is intended for a wide range of readers, hoping to provide readers with the recent scientific findings of why and how polyphenols can exert multiple health benefits.